The Relevance of Gordon’s Dividend Valuation Model and Earnings Multiplier in Stock Valuation - Bujang, Imbarine (2006)
The empirical finding suggested by Mansor and Lim (1992) is that approximately 75% of the analysts used to be speculators. Many investors in Malaysia want capital gain rather than dividends and for some investors focusing solely on dividend is not desirable. Norhayati (2005) found that about three quarter of the firms listed on the Kuala Lumpur Stock Exchange (KLSE) paid stable dividends which indicates the Gordon’s Model is relevant in appraising stock prices. However, due to arguments among analysts the model is considered irrelevant and the focus has been on the Earnings Multiplier Approach. The Earnings Multiplier Approach is more intuitive model which is less sophisticated, less formal, and easy to use. Shamsher, Annuar, and Chotigeat (1998) suggested that about 84% of the analysts prefer to use the Earnings Multiplier Approach in valuing the share prices.